Mixed gamification with virtual tools modify poor school performance - Holgado Quispe, Ana María (2023)
Currently, the use of gamifiers as teaching tools in virtuality is present due to the digital education that is developed in Latin America. The objective was to determine the effects of two methodologies: i) Mixed gamification; and ii) Usefulness of virtual teaching tools, in the cognitive processes of poor school performance. The methodology was experimental, quantitative. The evaluation was carried out on 150 Spanish-speaking schoolchildren, divided into three comparison groups (8.5 years of age ±0.4). They underwent 40 learning sessions with the D-S-F methodology (dynamics, strategy, feedback). The validated instruments were three performance tests on the areas of mathematics, science and communication. Significant results were obtained in cognitive processes from the activities designed with mixed gamification, although the effects were not decisive in the area of communication. It is concluded that gamification reduces low performance to raise cognitive processes for logical reasoning, cognitive deduction in mathematics, skills to generate hypotheses in science; and those of reading and oral expression. It is suggested to develop experiments with variables that include a digital evaluation of text writing, to avoid the limitations presented in this research.